How the immune system works - Sompayrac, Lauren (Wiley-Blackwell, 2012)
How the Immune System Works is not a comprehensive textbook. It's the book thousands of students have used to help them understand what's in their big, thick, immunology texts. In this book, Dr. Sompayrac cuts through the jargon and details to reveal, in simple language, the essence of this complex subject